Serum ST2 and hospitalization rates in Caucasian and African American outpatients with heart failure. (1st April 2020) - Savvoulidis, Panagiotis; Snider, James V.; Rawal, Sahil; Morris, Alanna A.; Butler, Javed; Georgiopoulou, Vasiliki V.; Kalogeropoulos, Andreas P.
Abstract: Background: Limited data exist on the association between circulating suppression of tumorigenicity 2 (ST2) and recurrent hospitalizations and emergency department (ED) encounters in outpatients with heart failure (HF). In addition, data on ST2 in African American patients with HF are scarce. Methods: We evaluated 307 outpatients with HF (age, 57 ± 12 years; 64.2% men; 51.5% Caucasian, 45.6% African American; median ejection fraction, 35%; ischemic etiology, 41.4%). Median ST2 was 37.8 ng/mL (29.6–51.4). Results: After a median of 3.1 years, there were 584 hospitalizations (224 for HF) and 335 ED visits (80 for HF). Patients (N = 176; 57.3%) with elevated (>35 ng/mL) ST2 had 2-fold higher hospitalization rates in adjusted models (rate ratio [RR] 1.97; 95% CI 1.38–2.82; P < 0.001), driven by 3.5-fold higher HF hospitalization rates (adjusted RR 3.56; 95% CI 1.69–7.49; P < 0.001). These associations persisted after adjusting for baseline B-type natriuretic peptide levels. Findings were similar for elevated ST2 and ED visit rates. Elevated ST2 was associated with the composite of death or HF hospitalization (109 patients; 3-year estimate: 35.4%); risk was 5-fold higher in the first 6 months but declined gradually. The higher hospitalization rates and composite endpoint risk associated with elevated ST2 was similar in African Americans and Caucasians. In landmark analyses in a subset of patients, 6-month (N = 112) and 12-month (N = 149) changes in ST2 levels from baseline added prognostic information. Conclusions: Elevated ST2 in outpatients with HF portends higher healthcare resources utilization and higher risk for accelerated disease progression, regardless of race, especially in the first 6 months. Highlights: In outpatients with HF, ST2 is strongly associated with 3-year hospitalization rates. ST2 levels had similar prognostic impact for African-American and Caucasian patients. The relative risks associated with elevated ST2 were higher for HF vs. non-HF events. Risk for death or HF hospitalization associated with elevated ST2 varied over time. Increases in ST2 after 6 or 12 months in a subset were associated with excessive risk.